Global nursing leadership: alive and kicking in the midst of the COVID‐19 pandemic. (15th September 2020) - Catton, Howard
Abstract: As the COVID‐19 pandemic continues its journey around the world, it has triggered a global nursing response, with nurses everywhere working to save the lives of their extremely sick patients. In parallel with the frontline response, the International Council of Nurses, the World Health Authority and the International Confederation of Midwives have used their biennial Triad meetings to set out what needs to be done from a global perspective to protect nurses and the people they serve. At a time of crisis, it is imperative that the world's nursing leaders, through ICN's National Nursing Associations, step up to give support and guidance at this historically unsettling time.